2011
DOI: 10.1007/s00213-011-2357-6
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical assessment of an adjunctive treatment approach for cognitive impairment associated with schizophrenia using the alpha7 nicotinic acetylcholine receptor agonist WYE-103914/SEN34625

Abstract: These data underscore the value of a preclinical evaluation of the adjunctive profile of a memory-enhancing agent in combination with antipsychotics and provide further support to augmentation with α7 nAChR agonists to address the cognitive deficits associated with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Evidence from animal and human studies have indicated that α7 nAChRs may serve as a therapeutic targets for improving cognition, memory, and sensory gating deficits in schizophrenia (Bitner et al, 2007; Freedman et al, 2008; Hajos and Rogers, 2010; Marquis et al, 2011; Rezvani et al, 2009; Young and Geyer, 2013). Numerous α7 nAChR agonists have shown to exert procognitive effects in preclinical models and some of them are currently in clinical development for cognitive symptoms of schizophrenia.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence from animal and human studies have indicated that α7 nAChRs may serve as a therapeutic targets for improving cognition, memory, and sensory gating deficits in schizophrenia (Bitner et al, 2007; Freedman et al, 2008; Hajos and Rogers, 2010; Marquis et al, 2011; Rezvani et al, 2009; Young and Geyer, 2013). Numerous α7 nAChR agonists have shown to exert procognitive effects in preclinical models and some of them are currently in clinical development for cognitive symptoms of schizophrenia.…”
Section: Resultsmentioning
confidence: 99%
“…The followup study, however, demonstrated that any contribution to antipsychotic activity through galantamine is primarily mediated via muscarinic, but not nicotinic, acetylcholine receptors (Wadenberg et al, 2011). Nevertheless, α7-nAChRs might also participate in antipsychotic activity because the α7-nAChR agonist WYE-103914/SEN34625 potentiated the efficacy profile of risperidone in the CAR test (Marquis et al, 2011). To our knowledge, WYE-103914/SEN34625 is the only α7-nAChR agent that has been tested in this model.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 86%
“…Recent studies have identified α 7 nAChRs as therapeutic targets for improving cognition, memory, and gating deficits in schizophrenia (Bodnar et al , 2005; Olincy et al , 2006; Bitner et al , 2007; Freedman et al , 2008; Rezvani et al , 2009; Hajos and Rogers, 2010; Marquis et al , 2011). This study in rats suggests that activation of α 7 nAChRs may have the added benefit of curbing motivation to smoke cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…This study also questioned whether local infusion of a selective agonist of α 7 nAChRs, PNU 282987 (Bodnar et al , 2005), into the NAc shell and anterior cingulate cortex would lead to reductions in responding maintained by NIC during PR. The α 7 agonists are currently being explored as therapeutics to improve cognition, working memory, and sensory-gating deficits in schizophrenia (Bodnar et al , 2005; Olincy et al , 2006; Bitner et al , 2007; Freedman et al , 2008; Rezvani et al , 2009; Thomsen et al , 2009; Hajos and Rogers, 2010; Castner et al , 2011; Marquis et al , 2011). A positive finding would have implications for smoking cessation therapies in general.…”
Section: Introductionmentioning
confidence: 99%